2021
DOI: 10.1038/s41598-021-83409-4
|View full text |Cite
|
Sign up to set email alerts
|

Harvest time affects antioxidant capacity, total polyphenol and flavonoid content of Polish St John’s wort’s (Hypericum perforatum L.) flowers

Abstract: The polyphenol content and antioxidant capacity of hyperforin and hypericin-standardized H. perforatum L. extracts may vary due to the harvest time. In this work, ethanol and ethanol–water extracts of air-dried and lyophilized flowers of H. perforatum L., collected throughout a vegetation season in central Poland, were studied. Air-dried flowers extracts had higher polyphenol (371 mg GAE/g) and flavonoid (160 mg CAE/g) content, DPPH radical scavenging (1672 mg DPPH/g), ORAC (5214 µmol TE/g) and FRAP (2.54 mmol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 49 publications
2
5
1
Order By: Relevance
“…Hypercum perforatum L. (Hypericaceae), is one of the most famous medicinal plants in the world. Its popularity is due to its wide range of medicinal applications [38][39][40]. In the literature, some authors also demonstrate the antimicrobial activity of H. perforatum extracts against Gram-positive bacteria [41][42][43], which is confirmed by our data.…”
Section: Discussionsupporting
confidence: 87%
“…Hypercum perforatum L. (Hypericaceae), is one of the most famous medicinal plants in the world. Its popularity is due to its wide range of medicinal applications [38][39][40]. In the literature, some authors also demonstrate the antimicrobial activity of H. perforatum extracts against Gram-positive bacteria [41][42][43], which is confirmed by our data.…”
Section: Discussionsupporting
confidence: 87%
“…These compounds and their structural analogs have already shown synergistic antioxidant effects and anti lipid peroxy radical properties [32,33]. The phenolic and flavonoid content of Hypericum specimens undergo significant quantitative alterations during the vegetative stages [34][35][36]. The total phenolic content of the samples S6, S9 and S10 were found to be in close agreement with the average phenolic content previously reported for Hypericum species (150.44 mg GAE/g of dried extract), using ethanol as extraction solvent.…”
Section: Fig 2 Hptlc Of Methanolic Extracts Visualized With Anisaldeh...supporting
confidence: 84%
“…The greater reduction observed here may be due to differences in substrate addition and replacement, or the study by Jafari et al [ 21 ] showed a linearly decreasing trend in total VFA with increasing doses of bamboo leaves, or both. Furthermore, it may be because the chemical compositions of plants are influenced by their geographic origin, harvest stage, and age [ 54 , 55 ]. The lower abundance of methanogenic archaea following PHN supplementation may support this result.…”
Section: Discussionmentioning
confidence: 99%